(untitled) (Raparin Journal of Humanities (RJH), 2025)
Sheikh Muhammad Ja’far al-Karbasi (1927 - 2016) represents an important phase in the linguistic correction movement in Iraq, especially in the last quarter of the past century. This is evident through his book "Views on the Mistakes of Creators," which made him famous and showed a different style and approach than those who preceded him in this field. He was distinguished by being one of those who combined the methods of leniency and strictness in linguistic correction. At times, he was strict, aiming for the most eloquent and accepting nothing less, while at other times, he was lenient, searching for the usages and justifications. Thus, he had a unique corrective approach. He was one of the prominent scholars of the Hawza (Islamic seminary) in Najaf and a Marja (religious authority) in his era. He left behind, during his 89 years of life, a significant scientific, jurisprudential, and linguistic legacy. His book was the first pioneering Iraqi attempt to frame common mistakes within the covers of a dictionary, and it is the second in the Arab world after "The Dictionary of Common Mistakes" by Muhammad Al-Adnani. Sheikh’s approach to linguistic correction can be determined based on it. He commented on the usages of journalists, academics, students, employees, and ordinary people, without exception, with phrases he extracted from what he heard from them in their usual daily usage. Sometimes, he directly concluded the term he wanted to verify, relying on important linguistic sources that amounted to a hundred works.